Pig manure treatment by filtration - Kowalski, Zygmunt; Makara, Agnieszka; Matýsek, Dalibor; Hoffmann, Józef; Hoffmann, Krystyna (Acta biochimica Polonica, 2013)
A study of new pig manure treatment and filtration process was carried out. The advantage of the worked out technology is the method of incorporation of crystalline phase into solid organic part of manure. The obtained new solid phase of manure contains about 50% of crystalline phase forming a filtration aid that enables high effectiveness of manure filtration. The filtration rate of manure separation into solid and liquid fractions with pressure filter may achieve 1300-3000 kg/m(2)/h. The method makes it possible to maintain an overall average pollutant removal performance 90% for the chemical oxygen demand COD, > 99% for the suspended solids SS, to 47% for the total nitrogen content. The obtained results showed that the proposed technology being efficient and simple offers a possible solution to pig manure problems.
Keywords: filtrace; průmyslová hnojiva; Filtration; Fertilizers; Animals; Swine; Manure; hnůj; prasata; Anaerobiosis; zvířata; anaerobióza